Improved Capacity Retention for a Disordered Rocksalt Cathode via Solvate Ionic Liquid Electrolytes. Issue 7 (25th April 2022) - Wichmann, Lennart; Brinkmann, Jan‐Paul; Luo, Mingzeng; Yang, Yong; Winter, Martin; Schmuch, Richard; Placke, Tobias; Gomez‐Martin, Aurora
Abstract: Lithium‐rich disordered rocksalts (DRX) are a promising class of cathode materials for high‐energy lithium ion batteries (LIBs) and lithium metal batteries (LMBs) due to the high initial specific capacities (>200 mAh g −1 ) as well as flexible chemical composition. However, challenges concerning severe capacity fade and voltage decay upon cycling at high cut‐off voltages are still to be overcome. Moreover, state‐of‐the‐art carbonate‐based electrolytes can be decomposed by reactive oxygen species released by DRX materials during cycling. In this work, the electrochemical performance of Li1.25 Fe0.5 Nb0.25 O2 (LFNO) || Li LMB and LFNO || graphite LIB cells is compared for a conventional, carbonate‐based electrolyte and the solvate ionic liquid (SIL) [Li(G3)][TFSI] (G3: triethyleneglycoldimethylether). Cycle life is notably improved by the chemically more stable ionic liquid electrolyte, as the anionic redox activity of LFNO is prolonged compared to the carbonate‐based cells. This work represents an important step toward an improved cycle life of DRX cathodes. Abstract : Expanding cycle life : Conventional carbonate‐based electrolytes decompose when paired with an oxygen‐redox based disordered rocksalt positive electrode. This work demonstrates how solvate ionic liquids can break the vicious cycle of electrolyte decomposition, growing internal resistances and voltage slippage to improve the cycle life of lithium ion as well as lithium metal batteries based on disordered rocksalt cathodes.